Meta-analysis of Acupuncture Efficacy on Nerve Root Cervical Spondylosis Therapy - Xunlu YIN; Liguo ZHU; Minshan FENG; Xu WEI; Jie YU; Long LIANG (康复学报)
Objective:To systematically review the efficacy and safety of acupuncture in the therapy of cervical spondylotic myelopathy.Methods:Randomized controlled trials (RCT) about acupuncture therapy on nerve root type cervical spondylosis were electronically searched in CNKI, PubMed, EMBase, Wanfang Data. After conducting quality evaluation according to the"bias risk assessment tool"in the Cochrane Collaboration, the results of Meta analysis were analysed by RevMan 5.3 software.Results:A total of 11 RCTs involved 974 patients were finally included. Meta analysis indicated that acupuncture combined with traction in the therapy of nerve root type cervical to improve spondylopathy pain relief [MD=-1.69, 95%CI (-2.63, -0.75) ];to improve the current pain conditions (PPI) [MD=-0.41, 95%CI (-0.56, -0.26) ];pain relief [VAS (McGill) ] [MD=-1.43, 95%CI (-2.21, -0.6) ];total pain score (PRI) [MD=-2.43, 95%CI (-4.06, -0.80) ];pain perception total score [PRI (S) ] [MD=-1.63, 95%CI (-2.07, -1.20) ];Pain Emotion Total Score [PRI (A) ] [MD=-0.89, 95%CI (-1.39, -0.38) ].The effect of acupuncture group in cervical spondylotic myelopathy therapy was better than that of the traction group, the difference was statistically significant (P<0.05).Conclusion:Acupuncture has good curative effect and advantage in the therapy of cervical spondylosis of nerve root type. However, there are many deficiencies in low-quality inclusion studies and heterogeneity between studies in this systematic review, large-sample, high-quality randomized controlled trials are necessary for validation in the future.